The Multifaceted Identity of Qur'anic Stories in QS. Hūd [11] - Mohsen Vazandeh (Esensia: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
This study examines the Qur'an's non-chronological narratives, arguing that their purpose goes beyond simply offering advice or lessons. The coherence of these stories suggests a strong link to the specific circumstances Prophet Muhammad faced during his mission. In other words, the way the stories are told seems to be influenced by the context in which they were revealed. This research explores the connection between the narratives and their historical context. It employs a qualitative method and the Sapir-Whorf Hypothesis, which suggests language shapes how we understand the world. Focusing on the narrative of Prophet’s portrayal within Surah Hud [11], this analysis reveals how the juxtaposition of character portrayal with consequences of defiance reinforces the Prophet's warnings against following ancestral beliefs. Furthermore, the inclusion of Mose’s story, unlike those of other prophets, Nūḥ, Hūd, Ṣāliḥ, Shua'ib, and Lūṭ, highlights the evolving nature of the message throughout Muhammad's mission. This research suggests a two-way relationship between the narratives and the changing context surrounding the Prophet.